Anatomic analysis of the equine mental foramen and rostral mandibular canal using computed tomography. (May 2018) - Rawlinson, Jennifer E.; Bass, Luke; Campoy, Luis; Broman, Ashton; Prytherch, Benjamin
Abstract: Objectives: To characterize the anatomy of the mental foramen and determine associations with age, weight, sex and breed. Study design: Retrospective descriptive study. Animals: Forty-one horses, 0.6–25.2 years and weighing 136–820 kg. Methods: Computed tomography (CT) studies of equine heads performed over 5 years were evaluated in multiplanar and three-dimensional reconstruction. Measurements obtained were positioning of the foramen along the mandible, foramen height and width, foramen–canal angulation and rostral canal mineralization. Exploratory statistical analyses investigated associations between measurements and age, weight, sex and breed. Results: Evaluation of 41 CT studies revealed foramen positioning was one-third of the horizontal distance of the incisor–premolar space from the second premolar and one-third of the vertical distance in the mandible from the dorsal surface of interproximal space at the level of the foramen. Age was negatively correlated to horizontal positioning [ r = –0.42; 95% confidence intervals (CI), –0.64 to –0.13]. Mean foramen width was 6.4 (range, 2.3–17.1) mm and height 5.6 (range, 2.1–10.3) mm. Age and foramen height ( r = 0.32; 95% CI, 0.01 to 0.57) and width ( r = 0.30; 95% CI, –0.01 to 0.30) were positively correlated. Thoroughbred and Warmblood/Draft horses had increased foramina heights compared with Quarter horses [analysis of variance (anova) p = 0.02]. Males had wider foramina (95% CI, –2.66 to 0.07). Angulation of the foramen–canal was mean ± standard deviation 68.3 ± 12.8° (range, 37.9–105.6°) transverse plane, 28.3 ± 4.1° (range, 18.2–39.0°) saggital plane and 41.4 ± 8.45° (range, 22.2–58.6°) dorsal plane. Older horses had decreased mineralization of the rostral canal (anova, left p = 0.015, right p = 0.025). Conclusions: The size, shape, positioning and angulation of the mental foramen varies. Mineralization of the canal is decreased in older horses. Clinical relevance: This study improves understanding of mental foramen anatomy and complications with needle placement.